Career Mentoring in Higher Education: Students' Perceptions and Experiences - Daniela Dumulescu; Diana Maria Sarca; Constantin Valer Necula (University Babes-Bolyai, 2020)
Nowadays, the process of building the career of emerging adults is embedded in the need for meaningful paths, connection, creativity and autonomy. Thus, the support services universities offer for students should incorporate subjective aspects of individual experiences such as targeting relevant goals, building meaningful learning experiences, promoting personal resources of adaptability. One of the most effective mechanism for positively influencing students' career paths is mentoring, by helping them to successfully face the academic and life challenges and to build meaningful careers. The current study aims to investigate perceptions and experiences of seven undergraduate students, in order to understand the mentoring role in the development of a calling orientation in their career trajectory. Data was collected through one-to-one semi-structured interviews and thematic analysis was conducted. The findings revealed a mentoring approach that includes a career construction theory and calling-infused elements has positive effects on self-reflection, self-knowledge, proactive experiences and behaviours that maintain and strengthens the perception of the presence of calling. In other words, the support of a mentor facilitates the activation of personal resources and values the self-directed career oriented towards individualized results in the context of an uncertain and dynamic work environment.